Valorization of Agroindustrial Waste from Tobacco (Nicotina Tabacum L.), Using it in Mixtures with Recycled Cellulosic Pulp, Office and Newspaper Paper for the Preparation of Molded Products - Albarrán-Molina, Eyra María (2025)
Lignocellulosic biomass refers to organic materials from plants and trees that contain cellulose, hemicellulose and lignin, which are firmly intertwined and chemically bonded in their cell walls. Additionally, these materials may contain other compounds such as extractives and foreign materials. Cellulose, hemicellulose and lignin are also the main components of natural fibers, which come from various resources such as wood, recycled fibers and agricultural biomass waste such as canola, wheat, rice and hemp straw. These fibers are mainly used for the manufacture of molded pulp products. Tobacco cellulose has similar properties to other cellulose sources, such as wood, and can be used to produce paper and other cellulose-based products. The fibrous material used in this study comes from agroindustrial tobacco waste (Nicotina tabacum L.), which was mixed with recycled cellulose pulp, from office and newspaper paper, for the production of moldable products. To transform the tobacco waste into particles, the hammer mill brand: CONDUX-WERK Wolfgang bei Hanau and model: LHM 20/16 was used. With a motor of: 1.5 Kilowatts / 2.01 HP Mechanical Horsepower, 380 V, 2820 rpm, 0.88 Cos Phi and 50 Hz. The factors selected for the experimental design of this study were the different types of paper used in the mixture: newsprint, office paper and tobacco, and said experimental design was carried out using the Statgraphics simulation software. The preparation and characterization of the raw material (tobacco, Nicotiana tabacum L.) was carried out using the Technical Report NREL/TP-510-42620 standards; where 70 g of each sample were weighed and then processed using the knife mill; These samples were sieved on a set of stacked sieves, where the upper one was 20 mesh and the lower one was 80 mesh. Thus, for the determination of moisture in this biomass, as well as for the determination of structural carbohydrates and lignin in biomass, the standards established in the Technical Report NREL/TP-510-42620 were also used, and for the determination of extractives in biomass, the standards established in the Technical Report NREL/TP-510-42619 were used. To prepare the tobacco fibers, a disc refiner, THE BAUEP BROS brand, was used. CO and model: 148-2, speed 2890 rpm. For the formation of the molds, a molding equipment was used and the corresponding tests were carried out according to the TAPPI T 402 sp-98 standard “Standard conditioning and testing atmospheres for paper, board, pulp handsheets, and related products”. In general, the results indicate that the tobacco (Nicotina tabacum L.) biomass sample has a high content of cellulose and hemicellulose (glucan and xylans), as well as a significant content of lignin; the average cellulose content being 32.61%, while hemicellulose 17.97% and lignin represents 20.71% of the cell wall composition; and a content of 13.58% of extractives and 10.11% of inorganic components.